The Holistic Impact of Omkar Chanting: A Narrative Review of it’s Physiological, Psychological and Acoustic Effects - Jayashree Pattanayak; Judu Ilavarasu (Journal of Clinical and Diagnostic Research)
Mantra chanting, being a timeless practice in Vedic literature, has fascinated scholars and practitioners alike in diverse traditions. It is one of the simplest yet most effective part of traditional yoga practices for millennia, particularly Omkar or Om chanting. Chanting of mantra brings clarity of thought, inner peace, and spiritual growth. The benefits of chanting can be understood both scientifically and spiritually, with the impact on multiple levels- mental, emotional, and even physical levels of the individual. Mantra chanting, particularly repetitive vocalisations, has been found to promote relaxation, reduce stress hormone levels, including meditative brainwave patterns. The review article discusses the multifaceted background of the Omkar mantra by tracing its significance. This article delves into the Vedic literature bridging its relevance in contemporary research. Through historical text analysis and recent scientific studies, the study aims to understand the potential benefits of the vocal practice of the Omkar mantra. The novelty of this review lies in how acoustic analysis of Omkar chanting affects psychological and physiological parameters evaluating the effectiveness of treatment approaches. The paper also discusses case studies and clinical findings that emphasise the potential benefits of regular Omkar chanting in mood improvement, rehabilitation of anxiety and depression, cognitive functioning, and its physiological impact on respiratory dynamics, heart rate variability, and neural activity. This article also proposes the future scopes for integrating acoustic analysis of Om chanting with different clinical applications research.